Epistemic citizenship under structural siege: a meta-analysis drawing on 544 voices of service user experiences in Nordic mental health services - Nouf, Faten; Ineland, Jens (Frontiers in Psychiatry, 2023)
This paper presents a meta-analysis, drawing exclusively on qualitative research [n=38], which contributes to findings on mental health service user experiences of received provisions and/or encounters in contemporary social and mental health services in the Nordic countries. The main objective is to identify facilitators of, and barriers to, various notions of service user involvement. Our findings provide empirical evidence regarding service users’ experiences of participation in their encounters with mental health services. We identified two overarching themes, professional relations and the regulative framework and current rule and norm system, in the reviewed literature concerning facilitators and hindrances of user involvement in mental health services. By including the interrelated policy concept of ‘active citizenship’ and theoretical concept of ‘epistemic (in)justice’ in the analyses, the results provide foundations for broader exploration and problematization of the policy ideals of what we call ‘epistemic citizenship’ and contemporary practices in Nordic mental health organizations. Our conclusions include suggestions that linking micro-level experiences to organizational macro-level circumstances opens up avenues for further research on service user involvement.